Sitaron ki shahzadi - Muhammad Younus Hasrat (Ferozsons (PVT) LTD Lahore, 2010)
Sitaron Ki Shahzadi is a magical story of a princess from the stars, whose celestial journey unveils the wonders of the universe and the power of dreams.